Aplikasi Langlang Saloka: Inovasi Teknologi untuk Meningkatkan Pengalaman Wisatawan (Jurnal Destinasi Pariwisata, 2025)
The tourism industry in Indonesia has great potential to continue to grow, one of which is through the application of digital technology. Saloka Theme Park, as one of the leading tourist destinations in Semarang, needs innovative solutions to improve visitor experience and operational efficiency. This research aims to develop the Langlang Saloka application with features of tourist history, online ticket booking, information on rides and facilities, and a complete address. The development process used FlutterFlow and Firebase, focusing on ease of use, accessibility, and user experience (UX). The results show that this application makes it easier for visitors to access information and increase comfort while traveling. Langlang Saloka is expected to be a digital innovation that supports the operational efficiency of tourist parks while contributing to the digital transformation of the Indonesian tourism sector.
Keywords: Travel App; Saloka Theme Park; User Experience; Flutter Flow; Firebase